PHASE: a Matlab-based software for the DInSAR PS processing - Monti, Roberto; Rossi, Lorenzo (Geodesy and Cartography, 2025)
The availability of free Synthetic Aperture Radar (SAR) images, like the ones delivered by the ESA Copernicus Sentinel-1 satellites, has led to the development of several processing tools, some of which are also free and open source. In this framework, when analyzing Sentinel data, the ESA SNAP software is usually required for data preprocessing, while, in the context of free and open source (FOS), Persistent Scatterer Interferometry (PSI) analysis can be performed by StaMPS (released by Stanford University). The workflow could be completed by the snap2stamps package, aiming at integrating the two main software packages. However, these tools are not designed to automate all the required steps to perform a complete PSI analysis. For this reason, the aim of this work is to develop PHASE (Persistent scatterer Highly Automated Suite for Environmental monitoring), a Matlab-based software suite that relies on already available FOS software, properly updated, enhanced and integrated, all accessible and customizable through a simple GUI. The focus is on minimizing the user interaction with the software, thus decreasing potential sources of error, while improving processing repeatability. The user will therefore primarily be responsible for configuring the processing parameters. Indeed, a streamlined procedure has been established, covering the entire process from downloading the SAR images to exporting the PS time series into a simple table format. In the paper, we present the developed software, highlighting its strengths compared to the status quo, while also providing a short example of successful application of the entire procedure.